Professional Master of Pharmacy Education in China - Liu, Yanli; Li, Hanhan; Pei, Yuyao; Wang, Yong; Yang, Changqing; Lu, Tao (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: The Professional Master of Pharmacy (M. Pharm.) education program in China has undergone 10 years of development and has rapidly achieved great progress. The aim of this study was to summarize and introduce the development of M. Pharm. education in China. Materials and Methods: The data related to M. Pharm. education in China was obtained from literature retrieval, the Ministry of Education of the People’s Republic of China (MOE), and related university websites. Some data was obtained from the Chinese National Steering Committee for the Professional Degree of Pharmacy Graduate Education (NSCPDP). The NSCPDP data was a result of questionnaires sent to 113 training institutions in 2021 and from a survey of recent graduates of China Pharmaceutical University (CPU) in 2019. Results: The main findings are that the training goals, degree education, qualifications and admission standards of institutions, training fields, curriculum setting, teaching methods, professional practice, faculty teams, quality assurances and evaluations, degree awarding and employment direction in the M. Pharm. education system are relatively well developed, and that M. Pharm. education has become an important part of pharmacy education in China. Conclusion: M. Pharm. education in China not only draws lessons from foreign advanced experience in the administration of schools and universities, but also has formed its own Chinese characteristics and emphasis. M. Pharm. education in China has a bright future through a program of continuous quality improvement.
Keywords: Professional master of Pharmacy; Education Program; Cultivation Model; Present and Future; China